Influences of Australian nursing students’ anxiety, depression, personality and family interaction on their psychological well-being and suicidal ideation - Pi-Ming Yeh; Lorna Moxham; Christopher Patterson; Carolyn Antoniou (Journal of Behavior Therapy And Mental Health, 2016)
Objective: To examine the relationships between Australian nursing students’ anxiety, depression, personality and family interaction with psychological well-being and suicidal ideation. Participants: A sample of 201 nursing students completed a series of structured questionnaires in an Australian University. Methods: A cross-sectional descriptive research design was used. After explanation of this study, 201 nursing students voluntarily participated. Six reliable and structured questionnaires were used to do data collection. SPSS was used for data analysis including descriptive data, Pearson Correlation, and Stepwise Multiple Regression. Results: Anxiety and depression were positively associated with suicidal ideation and had negative relationships with psychological well-being. Positive personality and family interaction were positively associated with psychological well-being and negatively with suicidal ideation. Parents’ harsh discipline had a negative relationship with the nursing students’ psychological well-being. Conclusions: Depression, personality, and positive family interaction were significant predictors of Australian nursing students’ psychological well-being. Anxiety, depression, and harsh discipline were significant predictors of suicidal ideation
Keywords: Australia